Four-armed Shiva on the lintel of the doorframe - Temples of India Project Team (Jio Institute, 2024)
The lintel of the doorframe depicts a seated, four-armed Shiva at the centre. On the proper right of the torana (ornamental gateway), a three-faced Brahma is shown standing, folding hands in veneration. On the other side, Vishnu is shown standing, holding a gaya (mace) and a chakra (discus) in his upper hands, while his front arms are joined in anjali hasta, in veneration to Shiva. Between these three divine figures, four horizontal bands are carved depicting gandharvas (celestial musicians), devotees, and ascetics worshipping the linga. At the topmost band, on the proper right side, matrikas (mother goddesses) are depicted along with Ganesha, while on the proper left side, navagrahas (nine planets) are represented.